2016
DOI: 10.1021/acsami.5b12324
|View full text |Cite
|
Sign up to set email alerts
|

Composite System of Graphene Oxide and Polypeptide Thermogel As an Injectable 3D Scaffold for Adipogenic Differentiation of Tonsil-Derived Mesenchymal Stem Cells

Abstract: As two-dimensional (2D) nanomaterials, graphene (G) and graphene oxide (GO) have evolved into new platforms for biomedical research as biosensors, imaging agents, and drug delivery carriers. In particular, the unique surface properties of GO can be an important tool in modulating cellular behavior and various biological sequences. Here, we report that a composite system of graphene oxide/polypeptide thermogel (GO/P), prepared by temperature-sensitive sol-to-gel transition of a GO-suspended poly(ethylene glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 69 publications
1
44
0
Order By: Relevance
“…[47][48][49] Contrarily, the weak forces such as hydrogen bonding and hydrophobic interactions are generated to support the stable hydrogel networks. 50,51 For examples, Yang et al reported a novel nanocomposite poly (2-acrylamido-2-methylpropanesulfonic acid)-based hydrogel with improved electro-responsiveness and mechanical properties by introducing reduced graphene oxide (rGO) sheets into poly(2-acrylamido-2-methylpropanesulfonic acid-coacrylamide) (poly[AMPS-co-AAm]) hydrogel network. 46 The prepolymerized solution containing AMPS, AAm, BIS, graphene oxide (GO) sheets, hydrazine hydrate, and ammonia solution is firstly treated by an ultrasound for 10 min to disperse GO sheets homogeneously in the solution [ Fig.…”
Section: Blending Nanomaterialsmentioning
confidence: 99%
“…[47][48][49] Contrarily, the weak forces such as hydrogen bonding and hydrophobic interactions are generated to support the stable hydrogel networks. 50,51 For examples, Yang et al reported a novel nanocomposite poly (2-acrylamido-2-methylpropanesulfonic acid)-based hydrogel with improved electro-responsiveness and mechanical properties by introducing reduced graphene oxide (rGO) sheets into poly(2-acrylamido-2-methylpropanesulfonic acid-coacrylamide) (poly[AMPS-co-AAm]) hydrogel network. 46 The prepolymerized solution containing AMPS, AAm, BIS, graphene oxide (GO) sheets, hydrazine hydrate, and ammonia solution is firstly treated by an ultrasound for 10 min to disperse GO sheets homogeneously in the solution [ Fig.…”
Section: Blending Nanomaterialsmentioning
confidence: 99%
“…Adipose tissue is another key component necessary for soft tissue reconstruction. Several studies have explored the effects of graphene‐based materials on adipogenic differentiation of stem cells . GO does not interfere with adipogenesis due to electrostatic binding with insulin, but pristine graphene greatly suppresses this process .…”
Section: Interactions Between Graphene Derivatives and Tissuesmentioning
confidence: 99%
“…Several studies have explored the effects of graphene‐based materials on adipogenic differentiation of stem cells . GO does not interfere with adipogenesis due to electrostatic binding with insulin, but pristine graphene greatly suppresses this process . In situ‐formed, GO‐incorporated hydrogels have shown excellent results as a 3D matrix for enhancing adipogenic differentiation of the incorporated stem cells …”
Section: Interactions Between Graphene Derivatives and Tissuesmentioning
confidence: 99%
“…The prepared NC hydrogel showed enhanced chondrogenic differentiation biomarker expression and chondrogenic differentiation of stem cells in the 2D/3D hybrid systems. Later, the same group reported the use of thermoresponsive PEG‐ L –PA/GO for the adipogenic differentiation of TMSCs . The PEG‐ L –PA/GO showed enhanced expression of adipogenic biomarkers, resulting in excellent adipogenic differentiation in comparison to both the graphene‐incorporated hydrogel and the hydrogel itself due to better adhesion of the adipogenic differentiation factor (insulin) on the large surface area provided by GO.…”
Section: Nanocomposite Hydrogels With Specific Propertiesmentioning
confidence: 99%